Identification of nitric oxide synthase as a protective locus against tuberculosis - MacMicking, John D. (The National Academy of Sciences of the USA, 1997)
Mutagenesis of the host immune system has helped identify response pathways necessary to combat tuberculosis. Several such pathways may function as activators of a common protective gene: inducible nitric oxide synthase (NOS2). Here we provide direct evidence for this gene controlling primary Mycobacterium tuberculosis infection using mice homozygous for a disrupted NOS2 allele. NOS2(−/−) mice proved highly susceptible, resembling wild-type littermates immunosuppressed by high-dose glucocorticoids, and allowed Mycobacterium tuberculosis to replicate faster in the lungs than reported for other gene-deficient hosts. Susceptibility appeared to be independent of the only known naturally inherited antimicrobial locus, NRAMP1. Progression of chronic tuberculosis in wild-type mice was accelerated by specifically inhibiting NOS2 via administration of N(6)-(1-iminoethyl)-l-lysine. Together these findings identify NOS2 as a critical host gene for tuberculostasis.